Bovine beta-casein micelles as delivery systems for hydrophobic flavonoids. (November 2019) - Li, Mo; Fokkink, Remco; Ni, Yuanying; Kleijn, J. Mieke
Abstract: The milk protein β-casein (β-CN) is an intrinsically unstructured amphiphilic protein that self-assembles into micelles. Naringenin is the main hydrophobic flavanone in grapefruit and has several beneficial biological effects: it exhibits, for example, antioxidant, anticancer and anti-inflammatory activity. This paper shows that naringenin can be encapsulated in β-CN micelles. Fluorescence spectroscopy, molecular docking modelling, dynamic light scattering (DLS), static light scattering (SLS) and isothermal titration calorimetry (ITC) were applied to characterize the effect of naringenin on the protein association behavior and properties of the resulting micelles. Naringenin binds to β-CN at both pH 7 and pH 2, promotes the formation of micelles with a well-defined size distribution and stabilizes the micelles. It was found that naringenin-containing β-CN micelles have a lower critical micelle concentration (CMC) and a larger aggregation number ( N agg ) compared to pure β-CN micelles. SLS and multi-angle DLS results suggest considerable differences between the structures of pure β-CN micelles and naringenin-containing β-CN micelles. In the presence of naringenin spherical micelles were formed with a relatively loose core ("hollow sphere"), while the pure β-CN micelles are smaller and seem to be elliptic. Notably, by uptake of naringenin in the micelles, the concentration of naringenin in aqueous solution could be raised considerably. These findings lead to the conclusion that β-CN micelles are very promising as effective delivery nano-vehicles for hydrophobic bioactive compounds. Graphical abstract: Image 1 Highlights: Naringenin binds to b-CN at both pH 7 and pH 2, promotes the formation of micelles and stabilizes the micelles. The concentration of naringenin in aqueous solution could be raised considerably. The structures naringenin-containing β-CN micelles have the considerable differences with that of pure β-CN micelles.